2008
DOI: 10.1088/0953-4075/41/20/205203
|View full text |Cite
|
Sign up to set email alerts
|

Collisional shifts and broadenings of doubly excited states of barium

Abstract: Shift and broadening parameters for doubly excited states of 5d6d, 5d7d, 5d7s, 5d8s and 6p2 configurations in neutral barium atoms are presented. A tunable dye laser pumped by an excimer laser was used to populate the Rydberg states of Ba by two-photon absorption from the 6s2 1S0 ground state. Inert gases Ar, Kr and Xe at 100 mbar pressure were used as perturbing gases. The resulting line shapes were fitted to a Voigt line shape function, from which shift and broadening parameters were inferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…For three inert gas perturbers, the nature of the graphs is the same except that the Xe perturber produces largest shifts and broadenings followed by Kr and Ar. As we showed in our previous publication on Rydberg states of Ba [12], these shift and broadening values could be verified by calculations based on electron scattering from inert gases. These calculations confirmed that the strength of interactions increased in the order of Ar, Kr and Xe.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For three inert gas perturbers, the nature of the graphs is the same except that the Xe perturber produces largest shifts and broadenings followed by Kr and Ar. As we showed in our previous publication on Rydberg states of Ba [12], these shift and broadening values could be verified by calculations based on electron scattering from inert gases. These calculations confirmed that the strength of interactions increased in the order of Ar, Kr and Xe.…”
Section: Resultssupporting
confidence: 84%
“…As we reported previously, in the case of Ba these perturbations also produce anomalies in the radiative lifetimes [9], Stark effects [10], forced auto-ionization and hyperfine structures [11]. Our recent study of Ba [12] identified several anomalies for the broadening and shift values for the same states. This was part of the motivation to explore similar examples in the case of calcium.…”
Section: Introductionsupporting
confidence: 70%